Eggs, oranges and other technological devices in science dissemination - Leão, Celina Pinto (2017)
The present work aims to analyze the challenge of organizing a science exhibition outside the common places (science museums, schools, universities). The exhibition, named "Scientist for a day", under analysis took place in a sports environment. It was organized by a group of five 15 years old athletes, supervised by three university professors, and attended by 120 participants. There were 12 experiments, from the simple Jumping Egg to the sophisticated Electromagnetic Levitation Plane and the eye-catching Wimshurst Machine. The analysis of the outlooks of the participants in this science dissemination activity was performed through questionnaires voluntarily answered by 59 attendees (aged between 3 and 64 years old). The survey was designed to investigate the level of satisfaction of the participants and their opinions regarding each experiment, identifying the most and the least preferred, and if they are considering further study at university and in what area. The results analysis is presented in terms of group age distribution. Summarizing the participants' perceptions, they were unanimous in recognizing that they were completely satisfied with the event.